PENGARUH KEBIJAKAN DIVIDEN TERHADAP NILAI PERUSAHAAN SAAT PANDEMI COVID-19 PADA PT PP PROPERTI TBK - Nasha Acacia Almira (Jurusan Administrasi Bisnis, FISIP, Universitas Lampung, 2020)
The purpose of this article is to determine the effect of dividend policy on company value during the COVID-19 pandemic at PT PP Properti Tbk. Dividend policy is the determination of the profits derived by a company that will be distributed to shareholders or retained earnings for additional capital. The value of a company is the value that reflects what price an investor is willing to pay for a company, the higher the stock price of a company, the more shows that the value of the company is higher. Coronavirus is a group of viruses that can cause disease in animals or humans, a type of coronavirus known to cause respiratory infections in humans. COVID-19 outbreaks in Indonesia are increasingly increasing. This is increasingly threatening companies in Indonesia. The decrease in net income will affect the amount of dividends to be given and give a bad signal to investors and potential investors. The decline in dividends that occur will affect the value of the company that will go down along with the decline in dividends during the COVID-19 pandemic.